Los recursos documentales del Servicio de Información sobre Discapacidad : Documentary sources in the Service of Information on Disability - Porras, P.; Sancho, I.; Verdugo, M. A.; Martín, R.; Vicent, C.; Díez, E. (Revista General de Información y Documentación, 2003)
This article discusses the contents of the Document sources of the Information Service on Disability (DIS) which focuses on dissertations and journal articles as these are considered to be of greater interest on account of their depth of analysis and research and their currency. A series of products are elaborated as information search aids: dossiers of documents grouped according to subject from different journals which offer the contents of the most relevant Spanish scientific journals on disabilities; a quarterly contents page bulletin giving the indexes of the most relevant national and international scientific journals. Thematic grouping of dossiers is carried out according to user demand and reports on issues suggested by users are also prepared periodically.